Tensions and coalitions: A new trade agreement affects the policy space for nutrition in Vietnam - Harris, Jody; Hrynick, Tabitha; Thien, Mai Thi My; Huynh, Tuyen; Huynh, Phuong; Nguyen, Phuong Hong; Thow, Anne Marie (Springer, 2022)
Global trade has shaped food systems over centuries, but modern trade agreements are hastening these changes and making them more complex, with implications for public health and nutrition transition. This study aimed to understand the impact of the 2018 Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) on the policy space for public health nutrition in Vietnam. We conducted comparative document review and key informant interviews, and our analysis drew on a framework of policy space and the theory of advocacy coalitions. We identified 10 CPTPP sections with potential public health nutrition implications; and 50 Vietnamese policies relevant to nutrition having one or more tensions with one or more CPTPP sections. A majority of policy tensions were in sections of the CPTPP relating to technical barriers to trade and government procurement; most tensions related to protecting policy-making from vested interests. Different groups of policy actors hold different beliefs and interests on these issues, and therefore promote different framings and policy approaches. We identified two advocacy coalitions working very separately on issues affecting nutrition policy space: a trade coalition holding the policy position that free trade improves nutrition by default; and a nutrition coalition holding the policy position that nutrition should be explicitly considered in trade policy. The policy space for nutrition in Vietnam has important potential constraints through written policy, and the trade and nutrition coalitions will need to interact more regularly and constructively in order to foresee where these tensions will arise in practice, and create plans for their mitigation. This study adds to global evidence of free trade agreement impacts on nutrition policy space, and we extend previous work by explaining these actor groupings in the policy space through the theory of advocacy coalitions.